O-1602, an Agonist of Atypical Cannabinoid Receptors GPR55, Reverses the Symptoms of Depression and Detrusor Overactivity in Rats Subjected to Corticosterone Treatment - Wróbel, Andrzej; Serefko, Anna; Szopa, Aleksandra; Ulrich, Daniela; Poleszak, Ewa; Rechberger, Tomasz (Frontiers in Pharmacology, 2020)
In view of the fact that GPR55 receptors are localized in brain areas implicated in the pathophysiology of depression, GPR55 gene expression is reduced in the dorsolateral prefrontal cortex of suicide victims, and GPR55 receptor agonism exerts an anxiolytic-like effect, GPR55 receptors have drawn our attention as a potential target in the treatment of mood disorders. Therefore, in the present study we wanted to check whether a 7-day intravenous administration of O-1602 (0.25 mg/kg/day) – a phytocannabinoid-like analogue of cannabidiol that belongs to the agonists of GPR55 receptors, was able to reverse the corticosterone-induced depressive-like behaviour accompanied by detrusor overactivity in female Wistar rats. Additionally, we tried to determine the influence of GPR55 stimulation on the bladder, hippocampal and urine levels of several biomarkers that play a role in the functioning of the urinary bladder and/or the pathophysiology of depression. Our experiments showed that O-1602 therapy improved signs of depression (measured by the forced swim test) and detrusor contractility (measured by conscious cystometry) in animals exposed to the corticosterone treatment. Moreover, the treatment reduced the oxidative damage in the urinary bladder and neuroinflammation (observed as the reduction of elevated levels of 3-NIT, MAL, and IL-1β, TNF-α, CRF, respectively). The O-1602 treatment also reversed the abnormal changes in the bladder, hippocampal or urine values of CGRP, OCT3, VAChT, BDNF, and NGF. The above-mentioned findings allow to suggest that in the future the modulation of atypical cannabinoid receptors GPR55 could have a potential role in the treatment of depression and overactive bladder.